Knowledge landscape of Treg research in breast cancer: a bibliometric and visual analysis - Wu, Zankai; Zhang, Yanting; Gong, Yiping; Hu, Jin (Frontiers in Oncology, 2024)
BackgroundRegulatory T (Treg) cells play a strategic role in maintaining immune homeostasis and their functions are closely linked to the development of different diseases, including cancer. This study aims to investigate the evolution patterns and popular research topics of Treg cells through bibliometric analysis.MethodThe Web of Science Core Collection database was used to extract publications related to Treg cells, which were then subjected to bibliometric analysis and visualization through VOSviewer, CiteSpace, and R software.ResultsBetween 2003 and 2023, a total of 666 articles were published. China and the United States had the highest citation counts, with Fudan University, Shanghai Jiao Tong University, and Tarbiat Modares University being the leading research institutions. Beckhove Philipp from the German Cancer Research Center and the National Center for Tumor Diseases in Heidelberg, and Christophe from the Cancer Research Center of Lyon, were the most prolific authors. Sakaguchi Shimon from the Immunology Frontier Research Center at Osaka University was the most cited author. “Frontiers in Immunology” published the most articles, while “Journal of Immunology” received the highest co-citations. Key terms in Treg research include immunotherapy, tumor microenvironment, prognosis, immunosuppression, and PD-L1. Among these, immunotherapy, prognosis, PD-L1, and immunosuppression have emerged as focal points of research in recent years.ConclusionWith active collaboration worldwide, research on Treg cells is rapidly advancing. Focusing on Treg cells as a potential target for cancer treatment shows great promise for future research, especially in terms of practical applications. This could offer valuable direction and fresh perspectives for further exploration of Treg cells in the medical field.